Effects of Different Parts of the Rose Flower on the Development, Fecundity, and Life Parameters of Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae) - Ding-Yin Li; Dan Zhou; Jun-Rui Zhi; Wen-Bo Yue; Shun-Xin Li (Insects, 2023)
Frankliniella occidentalis (Pergande) is an important horticultural pest that causes serious damage to rose plants, which is one of its preferred foods. In this study, rose petals, rose flowers, and 10% honey solution + kidney bean pods were chosen as foods to assess their influence on the growth, development and fecundity of F. occidentalis. The results showed that developmental time of immature F. occidentalis with the following trend: rose flowers <10% honey solution + kidney bean pods < rose petals < kidney bean pods. The longevities of both female and male adults were lowest when feeding on the rose petals and were highest when feeding on rose flowers. The fecundity was in the following order: rose flowers >10% honey solution + kidney bean pods > rose petals > kidney bean pods. The net reproductive rate (R0), intrinsic rate of increase (r), and finite rate of increase (λ) of F. occidentalis feeding on rose petals and kidney bean pods were lower than those feeding on rose flowers and 10% honey solution + kidney bean pods. The development, longevity, fecundity, and parameters have significantly changed since F1 generation after feeding with the three food types. The results indicated that different parts of rose flowers had a significant effect on the development of thrips, and nectar and pollen had a positive effect on thrips population increase and reproduction.